2021
DOI: 10.3389/fphar.2021.734351
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Derived ADAM17 Promotes Liver Metastasis in Colorectal Cancer

Abstract: Exosomes derived from cancer cells are deemed important drivers of pre-metastatic niche formation at distant organs, but the underlying mechanisms of their effects remain largely unknow. Although the role of ADAM17 in cancer cells has been well studied, the secreted ADAM17 effects transported via exosomes are less understood. Herein, we show that the level of exosome-derived ADAM17 is elevated in the serum of patients with metastatic colorectal cancer as well as in metastatic colorectal cancer cells. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…By inhibiting ADAM17 activity in liver CSCs, the broad-spectrum inhibitor of metalloenzymes TAPI-2 blocks Notch activation, responsible for a more aggressive phenotype [238]. CSCs derived from lung adenocarcinoma display high levels of MMP2, which contribute to highly invasive and migratory cell capabilities [242]. These few examples emphasize the relevance of ectoprotease inhibitors in targeting and eliminating CSCs.…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…By inhibiting ADAM17 activity in liver CSCs, the broad-spectrum inhibitor of metalloenzymes TAPI-2 blocks Notch activation, responsible for a more aggressive phenotype [238]. CSCs derived from lung adenocarcinoma display high levels of MMP2, which contribute to highly invasive and migratory cell capabilities [242]. These few examples emphasize the relevance of ectoprotease inhibitors in targeting and eliminating CSCs.…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
“…Exosomes transfer various molecules from tumour cells to immune cells and neovascular cells, contributing to the escape from immune surveillance and increased angiogenesis, respectively [231,245,246]. DPP4, APN, ADAM17, and MMP2/9 were recently described in EVs derived from solid and haematological tumours [242,[250][251][252][253][254][255][256][257]. For instance, DPP4 + exosomes in AML patients' plasma suppress the proliferation of normal haematopoietic progenitor cells, and, diprotin A, by inhibiting DPP4 activity, reverses the effects of exosome-mediated myelosuppression [251].…”
Section: New Avenues For Ectoproteases In the Context Of Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Meng et al proved the presence of large amounts of granulocyte–macrophage colony stimulating factor (GM-CSF) in exosomes, which have the potential to enhance the immunomodulatory function [ 44 ]. Sun et al demonstrated that patients with metastatic colorectal cancer had higher serum levels of exosome-derived ADAM17 and that exosomal ADAM17 could facilitate colorectal cancer cell migration by cleaving the E-cadherin junction [ 45 ]. Chen et al showed that neuronal apoptosis induced by necroptotic astrocyte-derived exosomes could be dramatically impaired by blocking pro-BDNF (brain-derived neurotrophic factor), suggesting that necroptotic astrocytes provoked neuronal apoptosis partially through exosome-derived pro-BDNF [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…EVs are divided into exosomes, oncosomes, microbubbles, and apoptotic bodies according to size, morphology and origin. Exosomes are widely distributed in saliva, blood, bronchoalveolar lavage (BAL) fluid, sputum, and other body fluids [ 40 ]. The cell membrane invaginates, forms endosomes, then forms multivesicular bodies, and finally secretes the bodies to the outside of the cell to become exosomes with a diameter of 30–100 nm.…”
Section: Introductionmentioning
confidence: 99%